Symptomatic Speech Disorders - Theoretical Basis and Practical Applications - Hanakova, Adela; Stejskalova, Katerina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Area of symptomatic speech disorders in person with sensory disabilities still stands on the edge of the interests of professionals. The article deals with the issue of speech therapy, special education of person with hearing impairment, and special education of person with visual impairment. Disruption of communication for people with sensory disabilities is one of the determinants of the quality of life. Within a broader theoretical framework symptomatic speech disorders in person with visual and hearing disability will be planted partial results of research with qualitative orientation. The exhibition will include in particular the issue of awareness, experience, access and awareness of speech therapists in the intentions of the issue.